Evaluation Of Lightning Performance 500 kV Extra High Voltage Transmission And Determination Of Critical Spots By Using Severity Index Method (Case Study on Paiton-Kediri 500 kV EHV Transmission) - YUDO PRAMONO (NIM 23205024), EKO
Theoretically, Extra High Voltage (EHV) 500 kV transmission lines are more robust against lightning strikes than EHV 150 kV or 70 kV. However, in case of EHV 500 kV Paiton-Kediri in Java, after five-years operation, many insulators were broken by lightning strikes, especially during rainy season. A large number of broken insulator deterioted performance of the lines, in which many line outages occurred. Based on that research must be done to get corresponding lightning performance of the line with involved the lightning characteristic of an area where the transmission passed, in order to calculated the lightning performance of 500 kV EHV Paiton-Kediri and to determine the tower which must be improve to fulfil performance of 500 kV EHV transmission that want by PT. PLN P3B Java Bali. The severity index method could be applied to determine the critical spots along that transmission line so we can know which tower will be improve according with an economically reason. The calculation of that index based on an historical lightning incidence in narrow strip along the line, and from evaluation of severity of lightning stress over the tower insulators for each tower along the line, with involved the tower parameters like tower height, tower altitude and tower footing resistance.